(untitled) - Harada, Jiro (Tokyo, 1937)
This book introduce about characteristics of the Japanese which have influenced, certain ideals and characteristics of Japanese art, a survey of Japanese archaeology. Japanese architecture.
Keywords: Nghệ thuật, Nhật Bản,Art, Japanese